The impact of the economic crisis on the human capital - PĂRĂLUŢĂ, Nedelea Chira (Annals of Spiru Haret University. Economic Series, 2010)
The dissertation refers to the impact of the economic crisis on the human capital. In order to underline the wide range of aspects related to this subject, I have analysed the labour market quantitative and qualitative indicators during the economic crises. The human capital is analysed having in view the evolution of the actual society towards an informational one, a process imposing qualitative and quantitative transformations in education and professional training.